Structural Changes in Stigmatella aurantiaca During Myxospore Induction - Reichenbach, Hans (1969)
Suspension cultures of Stigmatella aurantiaca (Chondromyces aurantiacus) were induced to form myxospores by addition of glycerol to the growing culture. The cells were fixed at various stages during conversion, thin sections were prepared, and changes in fine structure were studied. Vegetative cells are quite similar in their ultrastructure to Myxococcus xanthus. During transformation into myxospores, three important cytological changes were observed. Granules of storage material, probably polysaccharide and polyphosphate, accumulated; a 200 to 300-μm thick capsule was laid down, and the outer triple layer of the cell wall became locally folded. These cell wall folds were often densely packed and lay in pockets formed by the cytoplasmic membrane. We have suggested the possibility that the cell may store in these folds wall material which has become superfluous by the decrease in surface area during conversion.